Leaves of Olea europaea L. as a source of oleuropein: characteristics and biological aspects (Research, Society and Development, 2021)
Olive fruits, leaves and derived virgin oils are known to be good sources of polyphenols and other antioxidants that have recently received increasing interest. In addition, its derivatives are responsible for the bitter and spicy taste of green olive fruits and virgin olive oils. In the physiology of the olive plant, the enzymatic biotransformation of oleuropein is related to fruit ripening and the tissue-specific defense mechanism. The oleuropein is one of the main phenolic compounds identified in fruits and olive leaves. It has several pharmacological properties, including antioxidant, cardioprotective, anti-heterogeneous, neuropathic, anti-cancer and other effects. Oleuropein is slightly absorbed after oral administration and reaches a maximum plasma concentration, being widely distributed in various organs and tissues, including the heart, liver and brain. In view of recent studies on the use oleuropein obtained from olive leaves in the treatment and prevention of diseases, this work was carried out with the aim of compiling the main information available in the literature through this review.